Maslahah-Based Judicial Reasoning in Divorce Cases Involving Extramarital Relationships: A Case Study of The Gorontalo High Religious Court - Fitriyani; Budiman, Arman; Wafaa Yusof (Institut Agama Islam Negeri Kendari, 2026)
A marriage may remain legally intact on paper while, in reality, it has already collapsed under betrayal, emotional rupture, and irreparable harm. This study aims to analyze the philosophical, legal, and sociological arguments employed by the judges of the Gorontalo High Religious Court in deciding a divorce case involving an extramarital relationship, and to examine how the principle of maslahah is constructed within that judicial reasoning. Using a qualitative juridical case-study design, the research focuses on Decision Number 12/Pdt.G/2013/PTA.Gtlo and is supported by interview data with judges. The findings show that the judges’ reasoning was built through the integration of philosophical considerations of substantive justice, juridical considerations based on positive law, Islamic legal norms, and jurisprudence, as well as sociological considerations derived from the factual breakdown of the marital relationship. The discussion further demonstrates that the decision was substantively guided by a maslahah-oriented logic, particularly the principle of dar’u al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ, by which divorce was treated as a means of preventing greater harm when the continuation of marriage no longer served its essential purposes. This study concludes that maslahah provides an operationally valid framework for understanding judicial reasoning in appellate divorce cases within religious courts. The research implies that Islamic legal values are not merely theoretical references, but can function as practical judicial tools for aligning legal certainty, justice, and social reality in family law adjudication. Keywords: divorce cases; judicial reasoning; maslahah.